The Impact of Unconventional Monetary Policy on Gendered Wealth Inequality - Young, Brigitte (Papeles de Europa, 2019)
Unconventional monetary policy was implemented as a result of the financial crisis and resulted in rising asset prices in the stock markets. While the increase in asset prices is not exclusively triggered by unconventional monetary policy, central bankers accept that unconventional monetary policy has resulted in distributional effects on wealth, and that these are not negligible. What is missing are studies analyzing whether these non-standard monetary policies have different distributional effects on women and men. The intent of the paper is to interrogate whether unconventional monetary policy of central banks has a gender bias that operates in favor of men as gender and against women as gender. Relying on insights from feminist economics, the paper uses the results of the ECB Household Finance and Consumption Survey (HFCS) of 62,000 household across 15 euro-area countries. While the results are tentative, they show an asymmetric distributional gendered impact. Since the rich own more assets than the poor, and since monetary easing works in part by raising asset prices, these unconventional policies may unintentionally benefit the wealthier quintile (on average more male) at the expense of the poorer strata of society (on average more female).